(untitled) (Revista revoluciones, 2023)
Mining concessions are increasingly subject to social conflicts in which extractive activities are prioritized to the detriment of the collective rights of peasant and indigenous communities. In this sense, the Puno region is no stranger to this problem, as it is an issue of national relevance. Therefore, the general objective of this research is to analyze the collective perceptions of villagers on social, economic and environmental issues related to the proposed mining exploitation in the Chullumpi - Pichacani micro-watershed, located in Puno, Peru. The methodological approach used is qualitative, using a dialogic inductive-hermeneutic scientific method based on non-probability snowball sampling. Interviews were conducted with 18 people, both men and women, from different communities in the micro-watershed. The technique used for data collection was the semi-structured interview, using an interview guide as an instrument. The results describe the social, economic and environmental perceptions of the inhabitants in relation to the mining proposal. In the social area, the possible positive and negative impacts of the mining activity on aspects such as health and education are analyzed. In the economic sphere, the possible positive and negative changes that could occur in agriculture, livestock and marketing are examined. In the environmental area, the possible positive and negative impacts of the mining activity on water and soil are analyzed.